Pengaruh Faktor Financial Distress Dan Audit Fee Terhadap Audit Delay - Supriadi, Adi; Ginting, Jimmy Paulino (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
This research was conducted to determine the independent variable financial distress, audit fees and the dependent variable, namely audit delay. This research was conducted on property & real estate companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Financial distress affects audit delay. This can happen if a company has been identified as having bad finances because it is beyond the control of the company concerned, then the auditor needs to carry out further investigation to investigate the evidence that supports and causes the company's finances to become bad. Of course, this requires more time, so financial distress is said to influence the occurrence of audit delays. However, the sample used in this research is limited to using only Property & Real Estate Sub Sector companies listed on the Indonesia Stock Exchange within a period of 5 years, 2017-2021 period from a total of 62 companies so that the research results cannot be generalized in general to companies in Indonesia. The limited variables used in this research, such as audit fees, resulted in a decrease in the number of samples because there were no companies that included the audit fee amount in their financial reports. Because this research uses secondary data, data analysis relies heavily on data publications and company financial reports. This research only uses 2 independent variables, namely financial distress and audit fees, so this research still has many shortcomings.